2018
DOI: 10.3390/environments5040049
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Inland Pacific Northwest Wheat Farmers’ Perceived Risks: Motivating Intentions to Adapt to Climate Change?

Abstract: The Regional Approaches to Climate Change for the Pacific Northwest Agriculture (REACCH PNA) project was a USDA-National Institute of Food and Agriculture (NIFA) funded effort aimed at taking a comprehensive and interdisciplinary approach to understanding the implications of climate change on wheat and other cereal crop production in the inland Pacific Northwest (iPNW). As part of this project, two comprehensive surveys of wheat producers were conducted in 2012/13 and 2015/16, which included questions concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
(133 reference statements)
0
13
0
Order By: Relevance
“…For example, in Michigan, people's personal perceptions of climate change generally matched with historical climate and weather data , whereas others found that people's existing beliefs motivate what historical changes they believe they have observed (Myers et al 2013) or that risk perceptions are a stronger predictor of climate change belief than personal experience (Marlon et al 2018). Additionally, climate change perceptions, which are drivers of adaptation behavior and support for climate policy (Niles et al 2013, Roesch-McNally 2018 can be affected by personal experience with climate impacts (Spence et al 2011, Haden et al 2012 as well as socio-political factors (Hamilton and Stampone 2013). Therefore understanding how perceptions of climate change relate to experienced weather and climate-induced impacts is important to assess the influence of these varying causes on climate change belief and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Michigan, people's personal perceptions of climate change generally matched with historical climate and weather data , whereas others found that people's existing beliefs motivate what historical changes they believe they have observed (Myers et al 2013) or that risk perceptions are a stronger predictor of climate change belief than personal experience (Marlon et al 2018). Additionally, climate change perceptions, which are drivers of adaptation behavior and support for climate policy (Niles et al 2013, Roesch-McNally 2018 can be affected by personal experience with climate impacts (Spence et al 2011, Haden et al 2012 as well as socio-political factors (Hamilton and Stampone 2013). Therefore understanding how perceptions of climate change relate to experienced weather and climate-induced impacts is important to assess the influence of these varying causes on climate change belief and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-two per cent of these respondents indicated that they have already taken action to respond to climate change on their farms. It is clear that farmers from other parts of the country are also beginning to take action in response to climate change (Jemison et al ., 2014; White et al ., 2018; Schattman et al ., 2018 b ) and many farmers anticipate taking action in response to projected changes (Haden et al ., 2012; Niles et al ., 2016; Roesch-McNally, 2018; Roesch-McNally et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This work highlights the importance of gaining local, place-based information on farmer perspectives on climate change, their attitudes toward climate action and their need for climate-informed resources (Chatrachyan et al, 2017;Lane et al, 2018;White et al, 2018). This work is therefore a critical first step in providing a grounded perspective for county-based Extension, as a community of practice (Roesch-McNally et al, 2019), as they seek to provide services to small farmers who are dealing with challenges associated with climate change. Renewable Agriculture and Food Systems 629…”
Section: Climate Change Beliefs and Attitudes Toward Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important mostly in the eastern part of the analyzed region, where the main livelihood opportunity is related to 270 agriculture, and where the population should be aware that recent and more productive hybrids could be successfully cultivated under new climate conditions (Croitoru et al, 2020). Under these circumstances, a proactive policy could facilitate the sustainable transition to a more diverse agro-ecosystem, avoiding the path dependency associated with a monoculture production approach (Roesch-McNally, 2018).…”
Section: Analysis Clesovi 240mentioning
confidence: 99%